Improvement of a combined ultrasonic probe used in ultrasonic velocity-change method for evaluation of fat content. (18th June 2018) - Aotani, Yuhei; Kumagai, Yuta; Kameda, Masanobu; Wada, Kenji; Matsunaka, Toshiyuki; Morikawa, Hiroyasu; Horinaka, Hiromichi
Abstract: Fatty liver is a disease in which excessive fat accumulates in the human liver. Since fatty liver can be considered as an indicator of metabolic syndrome, early diagnosis of fatty liver is important. We have studied the ultrasonic velocity-change method as a noninvasive diagnostic method of fatty liver. In this study, a simple and highly sensitive ultrasonic probe was constructed by combining two transducers that orthogonally face each other; one of the ultrasonic transducers is used for warming and the other is for ultrasonic velocity-change detection. We also placed an acoustic mirror of the Al plate tilted at 45° in the combined probe that colinearly aligns two ultrasonic waves having different frequencies. By applying this probe to the ultrasonic velocity-change method to evaluate fat content rates, we could estimate them almost accurately even at the depth of 6 cm in the phantom.